2013
DOI: 10.1039/c3cp51394g
|View full text |Cite
|
Sign up to set email alerts
|

3D structure through planting core–shell Si@TiN into an amorphous carbon slag: improved capacity of lithium-ion anodes

Abstract: A 3D-structured anode material, planting core-shell Si@TiN into an amorphous carbon slag (3D STC), was synthesized via a facile pyrolyzing process in assistance with the low-temperature reduction route in a liquid Na-NH3 system. The as-prepared samples were characterized by X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, cyclic voltammetry and galvanostatic discharge-charge tests. From morphological analysis, TiN nanoparticles were homogeneously dispersed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…8 To improve the electrochemical performance, many studies concerning the silicon material, 5,9,10 the binder, [11][12][13] or the formulation 14,15 have been carried out. As an example, it has been shown that the use of silicon nanoparticles, which better accommodate volume expansion, [16][17][18][19][20] very much increases Si electrodes' cyclability. Whatever the preferred solution, the cycling performance of these electrodes, particularly in terms of the coulombic efficiency, has remained so far unsatisfactory for use in practical LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…8 To improve the electrochemical performance, many studies concerning the silicon material, 5,9,10 the binder, [11][12][13] or the formulation 14,15 have been carried out. As an example, it has been shown that the use of silicon nanoparticles, which better accommodate volume expansion, [16][17][18][19][20] very much increases Si electrodes' cyclability. Whatever the preferred solution, the cycling performance of these electrodes, particularly in terms of the coulombic efficiency, has remained so far unsatisfactory for use in practical LIBs.…”
Section: Introductionmentioning
confidence: 99%